2015
DOI: 10.1097/01.asw.0000460889.44609.0c
|View full text |Cite
|
Sign up to set email alerts
|

Modalities of Soft-Tissue Coverage in Diabetic Foot Ulcers

Abstract: From the results of this study, the authors conclude that radical debridement and soft-tissue cover in the form of a skin graft/flap is an effective method of managing DFUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…25,37 One study was excluded because further review revealed that the flaps mentioned did not meet the definition of a local random flap. 5 The remaining 25 studies that were scrutinized for data extraction shown in Table 1 had a total of 512 patients in whom 204 local random flaps were performed on 199 patients with diabetes mellitus to achieve definitive foot wound closure. Table 2 provides an overall description of the studies in our systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,37 One study was excluded because further review revealed that the flaps mentioned did not meet the definition of a local random flap. 5 The remaining 25 studies that were scrutinized for data extraction shown in Table 1 had a total of 512 patients in whom 204 local random flaps were performed on 199 patients with diabetes mellitus to achieve definitive foot wound closure. Table 2 provides an overall description of the studies in our systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search identified 53 eligible studies. 4-56 After applying the inclusion and exclusion criteria, 28 studies were excluded. Nine studies were excluded because they were performed on foot wounds in patients without diabetes mellitus *.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mainstay of treatment in diabetic lower extremity wounds has been negative-pressure wound therapy, skin grafts, or free flaps. 1…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach and medical advances in the past two decades have improved the ability to reconstruct complicated and infected diabetic lower extremities. Feet that once would have been amputated can now be managed by salvage procedures, with similar or even better functional outcomes compared to diabetic patients who undergo amputation [ 12 , 13 ]. In this scenario, it is fundamental to consider the option of a surgical reconstruction, rather than an amputation, when treating diabetic patients with complicated and infected DFUs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%